The availability in electronic format of books included in syllabi at university libraries. The Online Degree in Library and Information Science of the University of León - Arroyo Vázquez, Natalia; Alvite Díez, María Luisa; Rodríguez Bravo, Blanca; de Cos González Taladriz, Lucía (Revista General de Información y Documentación, 2023)
Libraries in universities that teach online or distance degrees face the difficulty of facilitating access to their students to the recommended bibliography of the subjects. This problem has spread to all universities during the Covid-19 pandemic. The most obvious solution is to acquire that bibliography in digital format. Documents included in the syllabi of the Online Degree in Library and Information Science of the University of León, the only one taught in Spain in this modality, are analyzed in this paper to know what percentage of the monographs is available in digital format, through library loan licenses or open access. Given the low percentage obtained, which does not reach a third of the monographs and is considered clearly insufficient, we reflect on the reasons, proposing measures that libraries and teachers can carry out, and we state the necessary digitization of the monographs.